Impact of Underwriter and Auditor Reputation, and Firm Age on IPO Underpricing: Evidence from the Indonesia Stock Exchange (2022–2024) - Ramadhan, Sandy Fajar; Sumani, Sumani (Journal of International Conference Proceedings, 2025)
This study aims to analyze the impact of underwriter reputation, auditor reputation, and company age on the level of underpricing returns of companies that have conducted initial public offerings on the Indonesia Stock Exchange in the period 2022-2024. The method used is a quantitative approach with multiple linear regression techniques and testing the coefficient of determination by using SPSS. The sample analyzed includes 155 IPO companies during the period 2022-2024. The companies listed as the object of the study were audited by auditors in the big four and non-big four categories. The companies had underwriters with varying reputations from the lowest to the highest. The results of the analysis show that underwriter reputation and auditor reputation have no effect on underpricing in IPO companies during period 2022-2024. However, the age of the company on underpricing is proven to have an effect on underpricing in IPO companies during the period 2022-2024.